Suppression of lignohemicellulosic degradation caused by Ganoderma boninense in oil palm during basal stem rot establishment using benzoic acid - Fernanda, Rozi (2022)
The palm oil industry is one of the most successful industries in the world in terms of agricultural crops towards economic growth and development in its producing countries. Indonesia and Malaysia have become the main producers of palm oil dominated approximately 85% of the total world production of palm oil. However, a decline in the production of this oil has been observed that occurred due to the presence of white-rot fungus Ganoderma boninense the causal pathogen of basal stem rot (BSR) disease causing the degradation in the lower part of the trunk. G. boninense degrades the major components of wood in the lower trunk makes a loss of its support to the palm, which eventually caused the palm to collapse. Inefficacy in controlling this disease could be the lack of understanding of how the pathogen establishes itself in the host and degrade the structural components of oil palm trees. One of the potential compounds that can be used to suppress the growth of G. boninense is benzoic acid (BA). BA belong to aromatic carboxylic acid group that has antifungal effect against many pathogenic fungi. Therefore, this study aimed to understand a step-by-step mechanism of structural degradation of oil palm by G. boninense and the effect of BA on suppression of G. boninense growth and enzymatic activities while maintaining the structural components of oil palm wood (OPW). The antifungal activity of BA at different concentrations against the growth and enzymatic activities of G. boninense were tested using OPW as the substrate. Further, the use of BA to strengthen the lignin structure in oil palm seedlings was evaluated. BA at a concentration above 5 mM successfully inhibited the growth of G. boninense in in-vitro study. The mechanism of pathogen suppression by BA was related to the disruption and depolarization of fungal cell membrane lead to the loss in membrane permeability and integrity and finally caused the alteration in morphological, anatomical, and ultracellular structure of fungal mycelia. The study on wood degradation by G. boninense in response to BA treatment showed that G. boninense simultaneously degrade all the components of OPW. A significant (P < 0.05) reduction in wood weight loss and wood chemical component was observed in the BA-treated woodblock at 5mM and above. BA significantly reduced the degradation of OPW depending on its concentration. Microscopic observation of wood inoculated with G. boninense showed that the severe damage in wood structure of untreated wood block in compare with treated wood block showing least damage in the wood structure. This was due to the suppression of the ligno-hemicellulolytic activity of G. boninense by BA. The observation at the nursery level showed that during the disease establishment, G. boninense colonized the plant's root tissue 10 to 14 days after inoculation, while BA-treated seedlings showed the slow disease progression that colonized the root tissues in 7 to 8 weeks after inoculation. BA affect the morphological, anatomical, and cellular structure of G. boninense unable them to produce lignohemicellulolytic enzymes for degradation of wood lignohemicellulose. In addition, BA induced the activity of defense-related enzymes that increase lignin biosynthesis in the oil palm seedlings. These findings could be useful in understanding the mechanism of G. boninense infection in OPW and contribute to the development of sustainable control of BSR disease.